Recruitment, Duplex Unwinding and Protein-Mediated Inhibition of the Dead-Box RNA Helicase Dbp2 at Actively Transcribed Chromatin. Issue 6 (27th March 2016) - Ma, Wai Kit; Paudel, Bishnu P.; Xing, Zheng; Sabath, Ivan G.; Rueda, David; Tran, Elizabeth J.
Abstract: RNA helicases play fundamental roles in modulating RNA structures and facilitating RNA–protein (RNP) complex assembly in vivo . Previously, our laboratory demonstrated that the DEAD-box RNA helicase Dbp2 in Saccharomyces cerevisiae is required to promote efficient assembly of the co-transcriptionally associated mRNA-binding proteins Yra1, Nab2, and Mex67 onto poly(A) +  RNA. We also found that Yra1 associates directly with Dbp2 and functions as an inhibitor of Dbp2-dependent duplex unwinding, suggestive of a cycle of unwinding and inhibition by Dbp2. To test this, we undertook a series of experiments to shed light on the order of events for Dbp2 in co-transcriptional mRNP assembly. We now show that Dbp2 is recruited to chromatin via RNA and forms a large, RNA-dependent complex with Yra1 and Mex67. Moreover, single-molecule fluorescence resonance energy transfer and bulk biochemical assays show that Yra1 inhibits unwinding in a concentration-dependent manner by preventing the association of Dbp2 with single-stranded RNA. This inhibition prevents over-accumulation of Dbp2 on mRNA and stabilization of a subset of RNA polymerase II transcripts. We propose a model whereby Yra1 terminates a cycle of mRNP assembly by Dbp2. Graphical abstract: Highlights: Dbp2 associates with chromatin in an RNA-dependent manner. Loss of Yra1–Dbp2 interaction leads to over-accumulation of Dbp2 on mRNA. Yra1 inhibits duplex unwinding by reducing RNA-binding activity of Dbp2. Yra1-dependent inhibition of Dbp2 prevents aberrant mRNA stabilization. Regulation of Dbp2 is critical for maintaining proper gene expression.